2016
DOI: 10.1108/apjba-02-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Safety management practices and safety compliance in small medium enterprises

Abstract: Purpose The purpose of this paper is to examine the role of safety participation as a mediator in the relationship between the six facets of safety management practices (i.e. management commitment, safety training, worker’s involvement, safety communication and feedback, safety rules and procedures, and safety promotion policies) and safety compliance. Design/methodology/approach A survey of 74 employees of small and medium enterprises (SMEs) in the northern region of Peninsular Malaysia was carried out. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 62 publications
(107 reference statements)
8
46
1
1
Order By: Relevance
“…38 Studies show that the learning culture has the greatest impact on management and organizational factors, and this is representative of the effective role of training in the safety culture of an organization. 30,39,40 As for resilience, organizations must be able to adapt to new and complex problems, and this calls for the capability to make critical decisions without having to wait for management guidelines at workplace. 41 In this domain, Zarrin and Azadeh investigated the effects of RE on health, safety, environment, and ergonomic management system by using Z-number cognitive map.…”
Section: Discussionmentioning
confidence: 99%
“…38 Studies show that the learning culture has the greatest impact on management and organizational factors, and this is representative of the effective role of training in the safety culture of an organization. 30,39,40 As for resilience, organizations must be able to adapt to new and complex problems, and this calls for the capability to make critical decisions without having to wait for management guidelines at workplace. 41 In this domain, Zarrin and Azadeh investigated the effects of RE on health, safety, environment, and ergonomic management system by using Z-number cognitive map.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars (e.g. Subramaniam, et al, 2016) have suggested for more attention and studies to be done on OHS in SMEs within the specific context and sector. Consequently, this study has attempted to fill the gap by providing more practical views on the extent of OHS management practices among construction SMEs in Malaysia.…”
Section: Previous Studies On Ohs Practices Among Smes In the Construcmentioning
confidence: 99%
“…Despite the previous studies conducted in Malaysia (e.g. Ismail, et al, 2012;Subramaniam, et al, 2016), OHS has almost exclusively focused on safety practices in other industries, while little has been undertaken on examining the extent of construction SMEs' OSH practices. In Malaysia, supporting the SMEs in managing health and safety risk should be the priority, due to the significantly greater proportion of SMEs in the construction sector (Manu, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the findings of McGonagle et al (2016) exhibited that PMCS has a positive relationship with safety performance behaviors (p < .001). While Subramaniam et al (2016) showed that PMCS was the most significant predictor of safety participation behaviors (β = 0.473, p < 0.01). Zohar (2014) also proposed that safety outcomes depend on employees' perception of honest management commitment to safety.…”
Section: Perceived Management Commitment To Safety (Pmcs)mentioning
confidence: 99%